The Development of Organic Agriculture in Serbia and Worldwide - Golijan Jelena (Sciendo, 2021)
Organic agriculture is a food production system that sustains the health of people, soils and ecosystems with no adverse consequences, combining tradition, innovation and science. The development of such type of agricultural production, from its beginnings to the present day, has encompassed a number of specific stages both in Serbia and worldwide. Accordingly, the purpose of this survey study is to present the developmental course of organic agricultural production in Serbia and worldwide. The paper also summarises the state of organic plant production across different regions of Serbia, arguing that the Serbian organic production has been increasing since the 1990s. Following the political changes in Serbia in 2000, foreign donations, investments and organisations have significantly enhanced the country’s organic production sector as a whole. The largest number of organic producers (1/3) and the largest areas devoted to organic farming are concentrated in Vojvodina.